Curriculum Development Model on Disaster Mitigation Training in Islamic Perspective - Kheriawan, Kheriawan; Raihan, Raihan; Puadah, Popi (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to develop a Disaster Mitigation Training Curriculum Model from an Islamic Perspective (MBPI). The research employed a Research and Development (R&D) approach using the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The study was conducted at the Disaster Management Training Center (Pusdiklat PB BNPB) in Sentul, Bogor. Data were collected through closed and open-ended questionnaires involving 94 respondents from various professions, along with in-depth interviews with religious leaders and academics. Data analysis techniques included descriptive statistics using SPSS and thematic analysis using NVivo. The needs analysis results showed a positive response with an average score of 88.44% (categorized as good). The MBPI curriculum was structured into three parts: basic, core, and supplementary, with emphasis on the values of monotheism, worship, and social solidarity in the disaster context. The training was conducted over three days with 36 participants, resulting in an average class score of 88.47. Evaluation findings confirmed that the MBPI curriculum is feasible for implementation and was endorsed by experts as a model for Islamic-based disaster mitigation training. The study concludes that the MBPI curriculum is relevant to be applied nationally through BPBD, BPSDM, and the Ministry of Religious Affairs as a disaster education policy strategy integrated with Islamic education.